Extraction of Chrysanthemum morifolium Extractum by Ethanol Modified Supercritical CO2 - Jin, Jian-Zhong; Wen, Ming (Asian Journal of Chemistry, 2015)
In this study, ethanol modified supercritical CO2 extraction of Chrysanthemum morifolium extractum was optimized by single factor and orthogonal array design methods with respect to the effects of extracting pressure, extracting temperature, extracting time, flow rate of CO2, ratio of liquid to solid and ethanol concentration on the yield of Chrysanthemum morifolium extractum. The optimum extracting parameters were established with extracting pressure 30 MPa, extracting temperature 45 °C, flow rate of CO2 10 kg h-1, ratio of liquid to solid 15 mL g-1, ethanol concentration 95 % and extracting time 2 h. Under such conditions, the yield of Chrysanthemum morifolium extractum was 29.34 %. The content of flavonoids in Chrysanthemum morifolium was 12.46 mg g-1.